Numerical study of water-glycerol BA-LIFT: Analysis and simulation of secondary effects. (March 2021) - Moreno-Labella, J.; Munoz-Martin, D.; Márquez, A.; Morales, M.; Molpeceres, C.
Highlights: Phase field model allows to follow the fluid interface in BA-LIFT simulations. The velocity field generated by the blister cause a cavitation bubble. The presence of a cavitation bubble explains the occurrence of secondary effects. Fluid thickness uncertainty disturbs the repeatability of the process. Abstract: In Blister-Actuated Laser-Induced Forward Transfer (BA-LIFT), a laser pulse generates a blister in an intermediate polyimide layer to push away the fluid. In this work, a Phase Field model has been proposed to study the transference mechanisms. Simulations and experimental shadowgraphy images for BA-LIFT of water-glycerol mixtures have been compared. The transference mechanism in BA-LIFT is ideally only mechanical and does not explain some secondary effects in the jet expansion that have already been described in other LIFT techniques and associated with the cavitation of a thermally generated vapor bubble. The numerical model can reproduce the expansion of the main jet. The addition of a second push at 9 μs delay allows reproducing the secondary effects. Four possible causes of the second push have been studied: absorption of the laser pulse in the fluid, thermal conduction through the polyimide layer, a mechanical rebound of the elastically deformed blister, or pressure fall due to fluid velocity. After the analysis, the first three explanations have been rejected, and a hypothesis is proposed: the velocity field generated by the blister produces a cavitation bubble in the interface between the polyimide layer and the fluid, whose effects would be the same than the cavitation of the vapor bubble in other LIFT techniques.